Difference between revisions of "P. 186, line 6"

From Bill Goodwine's Wiki
Jump to navigationJump to search
(Created page with "The equation should be <math>a_{n+1} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.")
 
Line 1: Line 1:
 
The equation should be
 
The equation should be
  
<math>a_{n+1} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.
+
<math>a_{n+2} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.

Revision as of 16:45, 28 October 2011

The equation should be

.